PENGAWETAN LIMA JENIS KAYU UNTUK PERUMAHAN SECARA RENDAMAN DINGIN DENGAN BAHAN PENGAWET CCB - Sasa Abdurrohim; D Martono (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
Investigation about the cold-soaking treatment has been conducted on five wood species (i.e. keruing, nyatoh, melur, pulai and meranti merah) for housing purposes. The penetrating preservative for this case was CCB (copper-chrome-boron) chemicals. Before being treated. the wood specimens measuring 3 - 5 cm (in length) by 3 - 5 cm (in width) were prepared from each of the five species. Such specimens could not be treated by implementing the conventionally prescribed treating schedule. because the measurement of preservative retention at such schedule should follow the revised standard/schedule which differed from the conventional one. Hence, in cold-soaking treatment using CCB preservative, the specimens of wood species for such purpose had to be modified in their sizes/shapes.Three different sizes/shapes were prepared, i.e. beam, truss, and rafters; and then were allowed to reach their air-dry moisture contents. Afterwards. they underwent cold-soaking treatment using CCB preservative in two different concentrations (i.e. 5 percent and 10 percent). Meanwhile. the soaking durations implemented for each concentration were consecutively 3,5 and 7 days.The results revealed that all the wood species in all three sizes/shapes (i.e. beam. truss. and rafters)could be treated using the revised schedule. Except for meranti in truss and rafter. Related as such. the revised treating schedule for these five species has been appropriately devised.